Analisis Kebijakan Sertifikasi Dosen Dan Penguatan Profesionalisme Akademik Dalam Meningkatkan Mutu Pendidikan Tinggi - Ningarumsari, Rike Junia; Ailya, Ashima; Wasliman, Eva Dianawati; Wasliman, Iim (Jurnal Ilmiah Wahana Pendidikan, 2026)
The lecturer certification policy has been implemented to enhance academic quality and professionalism in higher education. This study focuses on the implementation of the lecturer certification policy at STIT Al-Ihsan Baleendah and its impact on lecturers' professional practices. The objective is to gain an in-depth understanding of how certification is carried out and its contribution to improving educational quality. This research is grounded in bureaucratic decision-making theory, a systemic approach to public policy, and the concept of academic professionalism. Employing a descriptive qualitative method, data were collected through observation, in-depth interviews, and document analysis. The findings reveal that the certification policy has encouraged improvements in teaching readiness, involvement in curriculum development, and academic productivity. However, challenges persist, such as the dominance of one-way teaching methods and low motivation among lecturers to engage in research and community service. This study recommends strengthening institutional support, continuous professional development, and contextual evaluation of certification practices within Islamic higher education institutions.